Morphological diversity of coleoptera (Arthropoda: Insecta) in agriculture and forest systems - Pompeo P.N.* (2017)
© 2017, Revista Brasileira de Ciencia do Solo. All rights reserved.Coleopterans (Coleoptera) are major ecosystem service providers. However ecomorphological features that are comparable in a wide range of invertebrates within this group and in various environments must be found, to be able to study regions with different species, contributing to overcome difficulties of the taxonomic approach and understand the functioning of ecosystems. This research addressed the diversity of Coleoptera, using a methodology of ecomorphological traits, as well as their relation with the land use systems (LUS) and the soil properties. The following LUS were evaluated: no-tillage (NT), croplivestock integration (CLI), pasture (PA), Eucalyptus stands (EST), and native forest (NF). Samples were collected using a 3 × 3 point grid (sampling points at a distance of 30 m), in winter and summer, in three municipalities on the Southern Santa Catarina Plateau, Brazil. Coleopterans were collected using the methodology recommended by the Tropical Soil Biology and Fertility Program, based on the excavation of soil monoliths, and on pitfall traps. To evaluate the biological forms (morphotypes) and ecomorphological groups, the ecomorphological index (EMI) methodology was adopted and the modified soil biological quality (SBQ) index was determined. At the same points, samples were collected to evaluate environmental variables (soil physical, chemical, and microbiological properties). Density data underwent nonparametric univariate statistical analysis and multivariate abundance to verify the distribution of coleopterans in the LUS, and the environmental variables were considered as explanatory. Regardless of the LUS, 14 morphotypes were identified, and adult coleopterans with epigean morphologic adaptations were more abundant than hemi-edaphic and edaphic coleopterans, respectively. Morphotype diversity was higher in the systems NF, EST, and PA in summer and in NT in winter. The reductions in SBQ index were not associated with a gradient of land use intensification (NF> EST> PA> CLI> NT), and the index was higher for NF and lower for EST. Principal component analysis (PCA) indicated a different distribution of invertebrates between the LUS. For the edaphic species, better adapted to life in the soil, a relation with NT and CLI was observed, due to more favorable pH values and phosphorus content. In the NF, a greater amount of morphotypes was identified, and the properties related to soil carbon dynamics contributed to explain this distribution. Separation at the morphotype level, taking adaptation level to soil life into consideration, has proved efficient to discriminate the LUS, mainly along with other explanatory environmental variables.